Development of Military Role in Indonesian Government - Yusa Djuyandi (Journal of Governance, 2023)
The presence of the military in the history of the Indonesian government has long strengthened Indonesia's independence. The military itself has had various impacts on the Indonesian government, including acceptable impacts, good impacts, and bad impacts. Indonesia is trying to create a professional military, which could increase demotions and reduce the military's opportunities for politics. However, there are many obstacles that hinder the success of a professional military and reduce the military's influence in the Indonesian government. After the era of demands for reform and the dismissal of the military from the government, people began to realize that it was difficult for the government and the military to become one. If forced, there will be dysfunction in government institutions. This analytical study concerns the need for a supervisory role in order to improve civil-military relations. Continuous and ongoing monitoring can improve civil-military relations and achieve democratization in civil-military relations. However, until now, the supervision between civilians and the military has not gone well. This happens because of the minimal participation of the government, which supervises and regulates the military, so that there is no arbitrariness in carrying out its duties and relations with civil society.